(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the concept of competence, professional competence, competence approach, professionally competent teacher, if the formation of professional competence of teachers of senior classes is a psychological problem, some work that needs to be done, the concept of competence in professional competence and the need to focus on the forms of theoretical training of teachers of senior classes in the formation of professional competence.